Women's decision making process about hormone replacement therapy in the New Zealand context : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Psychology at Massey University - Radford, Wendy Lena (Massey University, 2003)
The transitional time of menopause has differential meanings for mid-aged women around the world. The medicalisation of menopause has resulted in the increasing promotion of hormone replacement therapy (HRT) both to alleviate distressing symptoms and prevent future illnesses. It is against a background of constantly changing information that women have to make a complex decision about the benefits and risks of this therapy for short and long term use. The theory of planned behaviour (TPB) (Ajzen, 1985) has been successful in predicting a range of health behaviours but few studies have been conducted to assess its predictive validity on intention to take HRT and to date there has been no assessment of this model in the New Zealand context. The present study was undertaken to discover the factors that influenced decision making about HRT use in New Zealand and to predict women's intention to take it at menopause by applying the TPB. A cross sectional postal survey of 140 mid-aged women randomly selected from the General and Māori electoral rolls measured attitudes, subjective norms and perceived behavioural control as well as moral norms and similar prior behaviour. Results of hierarchical multiple regression analysis supported the utility of the TPB to predict intention to use HRT and also showed that moral norms made a significant independent contribution to the prediction of intention to use HRT. The most important factors that influence New Zealand women's intention to use HRT are both the views of people who are important to them and their own attitudes to this treatment. Having a personal sense of control over following the HRT regime and believing it is right to do so and not a sign of weakness are also important considerations. Taking the contraceptive pill in the past has no influence on the decision making process about future HRT use.
Some Appendix in Maori
Keywords: Hormone therapy; Menopause; Decision making; Maori Women; Health behavior -- New Zealand; Health and hygiene